(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Thysanoptera communities present in a vineyard agro-ecosystem in Piedmont, Northern Italy, were studied. Samples were taken mainly from two vineyards dudng 1991 and 1992. Samples of the vine and of the spontaneous flora were collected taking different organs individually: leaves, flowers, bark as well as turf and litter. The environment is characterised by a well-diversified vegetation. Samples of 55 plant species have been collected, 12 of those are woods or shrubs and 43 herbaceous. Thysanoptera community consists of 44 species. Two of them, Thrips albopilosus Uzel and T. hukkineni Priesner, are new to the Italian fauna. This Thysanoptera fauna can be subdivided in 6 minor communities (both phyllophilous and anthophilous living on crops, trees and weeds). All of them except the phyllophilous herbaceous one have a rich, typical and well-diversified composition. The phyllophilous ones are the most diverse. T. tabaci is the only species that is dominant in almost all the habitats. T. major is abundant on grape flowers and on tree leaves and flowers. Thrips fuscipennis is very important on wood leaves and vine leaves and flowers. Chirothrips manicatus and Ceratothrips frici are dominant species on grass and Dycots flowers respectively and Drepanothrips reuteri on grape leaves. There are important interactions among the different environments. T. major and T. fuscipennis move between the arboreous flora and the vines. T. tabaci breeds on weeds in spring and in summer moves to vines and trees. Predatory thrips often move from spontaneous vegetation towards vineyards tao. Overall positive influences of wild flora on the agro-ecosystem are prevalent.